Measurement of 4He charge- and mass-changing cross sections on H, C, O, and Si targets in the energy range 70-220 MeV/u for radiation transport calculations in ion-beam therapy - Horst, Felix; Brons, Stephan; Haberer, Thomas; Mairani, Andrea (Physical review, 2019)
Measured charge- and mass-changing cross sections for the systems 4He+12C, 4He+16O, 4He+28Si, and 4He+1H in the energy range 70-220MeV/u are presented. The cross sections were obtained via the attenuation method where a ΔE−E scintillator telescope was used for particle identification. These new data have particular relevance for future applications of 4He ions in ion-beam radiotherapy because this technique relies on precise heavy ion transport models for an accurate dose calculation. The radiation transport codes applied for this purpose typically make use of parametrizations of the total reaction cross section σR. The widely used parametrization for nucleus-nucleus reaction cross sections by Tripathi et al. is shown to underpredict the new experimental cross sections for 4He ions in the therapeutic energy range by up to 30%, which can lead to considerable dose calculation uncertainties. Therefore, modifications of the parameters in the Tripathi model are proposed to optimize it for applications related to 4He ion-beam therapy.